Peran Desa Wisata Kampung Durian terhadap Perubahan Norma Sosial dan Penguatan Identitas Lokal Masyarakat Desa - Mayesa Yuswijayanti; Moch Iqbal (Al-Khidmah : Jurnal Pengabdian dan Pendampingan Masyarakat, 2025)
This study aims to examine the impact of the Kampung Durian Tourism Village on the changes in social norms and the strengthening of the local identity of the village community. With the growth of the tourism sector, particularly village tourism, significant changes have occurred in various aspects of community life, including social norms and cultural values upheld by the community. This research employs a qualitative approach with a case study method focusing on the Kampung Durian Tourism Village in District X. Data were collected through in-depth interviews with local residents, tourism village managers, and participatory observation at the research site. The findings indicate that the presence of the Kampung Durian Tourism Village has led to changes in the community's social norms, such as shifts in interpersonal and family interactions, and has influenced the younger generation's perspectives on local wisdom. On the other hand, the development of this tourism village has also reinforced the local identity by reviving and preserving traditional practices and culture that were previously at risk of being forgotten. The management of the tourism village, based on local wisdom, has proven effective in maintaining and introducing traditional culture to tourists, while also raising awareness about the importance of preserving social values within the community. This study is expected to provide insights into the positive impact of tourism on social changes in rural areas and efforts to maintain the sustainability of local cultural identities.